A catalyst system comprising a trialkylsilyl phenolic compound and its preparation and use
By using a catalyst system of trialkylsilylphenol compounds and inorganic oxide supports, the problems of tube blockage, electrostatic sensitivity, and high oligomer content in existing Ti/Mg composite catalysts were solved, achieving efficient olefin polymerization, improving polymer performance, and reducing production costs.
Patent Information
- Application Number
- CN202211244303.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-10-12
AI Technical Summary
Existing Ti/Mg composite catalysts suffer from problems such as tube blockage, high electrostatic sensitivity, high oligomer content, and low efficiency in olefin polymerization, which affect polymer performance and production costs.
A catalyst system was formed by reacting trialkylsilylphenol compounds with inorganic oxide supports, magnesium halides, titanium halides, and electron donor compounds. The catalyst was prepared by spray drying and activated by adding organoaluminum compounds for use in olefin polymerization.
It improves catalyst activity, reduces hexane extract content and oligomer content, increases polymer melt index, is suitable for gas-phase fluidized bed polymerization, and reduces production costs.
Smart Images

Figure BDA0003885744330000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of olefin polymerization catalysts, specifically relating to a catalyst system containing trialkylsilylphenol compounds, its preparation method, and its application. Background Technology
[0002] Catalyst systems containing Ti / Mg complexes are commonly used in the polyolefin industry. Univation's UNIPOL process for polyethylene production initially used the M-1 type catalyst (UCAT-A) with silica gel as the primary catalyst. Because of the silica gel support, the catalyst exhibited high fluidity and mechanical strength, performing well in direct gas-phase fluidized bed applications and providing some control over polymer particle properties. However, with continuous production experience, the M-1 type titanium catalyst showed problems with the stability of solid feed, leading to issues such as pipe blockage and bridging. Simultaneously, the catalyst was highly sensitive to electrostatic discharge caused by impurities in the reaction system, resulting in reactor agglomeration and clumping. Furthermore, the M-1 type catalyst had low efficiency, resulting in high ash content in the resin product, leading to higher catalyst costs per unit product and affecting film quality. The J-type catalyst was developed to overcome the shortcomings of the M-1 type catalyst. While the main components of the J-type catalyst are basically the same as those of the M-1 type catalyst, there are significant differences in the preparation process. The J-type slurry polyethylene catalyst, by using slurry feed, overcomes the disadvantages of solid feed, such as difficulty in controlling the amount added, difficulty in uniform feeding, and the generation of static electricity. Moreover, due to the use of finer silica gel and a higher tetrahydrofuran content compared to the M-1 type catalyst, the catalyst activity is increased by 3 to 4 times.
[0003] In the homopolymerization of ethylene or the copolymerization of ethylene with α-olefins, the performance of the catalyst affects the properties of the polymer. While catalyzing the polymerization of ethylene, the catalyst produces oligomers. These oligomers alter the intermolecular forces of polyethylene, affecting the product's performance in use and processing, including its yield strength, elongation, and rigidity. The amount of oligomers is generally measured by the amount of hexane extract; therefore, the amount of hexane extract is also an important indicator of catalyst performance.
[0004] Chinese Patent CN106543303A relates to a catalyst component, a catalyst, and a method for preparing the same for olefin polymerization. The catalyst component comprises: 1) an ultrafine inorganic oxide support, and 2) reaction products of magnesium halide, halogenated hydrocarbons, titanium halide, and electron-donating compounds. The catalyst comprises reaction products of the following components: (A) the catalyst component described in this invention; and (B) a catalyst of the general formula AlR. n X 3-nThe present invention relates to organoaluminum compounds, wherein R is a hydrogen or a hydrocarbon group having 1-20 carbon atoms, X is a halogen, preferably chlorine, bromine, or iodine, and 0 < n ≤ 3. The catalyst of this invention exhibits high activity, resulting in a polymer with higher bulk density and a higher melt index. However, the catalyst prepared by this method has a high hexane extractable content in the polymer powder generated from ethylene homopolymerization, which has an adverse effect on industrial production.
[0005] Chinese patent CN101376680A discloses a catalyst component for ethylene polymerization or copolymerization, its preparation method, and the application of a catalyst composed of this catalyst component in ethylene polymerization or copolymerization. It involves supporting at least one inorganic titanium compound, at least one organic titanium compound, at least one electron donor, and at least one activator on a magnesium / titanium-containing solid. This invention provides a highly efficient, hydrogen-sensitive solid catalyst component that yields polymers with low fine powder content. It has a relatively narrow particle size distribution and a small average particle size, exhibiting high catalyst activity. It is suitable for slurry polymerization or gas-phase polymerization of ethylene, and is particularly suitable for gas-phase fluidized bed polymerization processes where the catalyst is fed in slurry form. However, industrial trials show that this catalyst is not well-suited for high-load, high-condensation-rate fluidized bed production processes, and is prone to powder sticking. Summary of the Invention
[0006] To address the aforementioned shortcomings of existing technologies, this invention provides a catalyst system comprising trialkylsilylphenol compounds, and uses this catalyst system as a catalyst for olefin polymerization. The catalyst system provided by this invention contains metal components and silylphenol compounds, resulting in higher catalyst activity. Furthermore, the inorganic oxide support added to the catalyst components exhibits good dispersibility in the catalyst system, further enhancing the catalytic effect.
[0007] One of the objectives of this invention is to provide a catalyst system comprising a trialkylsilylphenol compound, including an inorganic oxide support and a product obtained by reacting a trialkylsilylphenol compound, magnesium halide, titanium halide and an electron donor compound.
[0008] According to an embodiment of the present invention, the general formula of the trialkylsilylphenol compound is R3Si-Ph-OH, wherein R is selected from at least one of H, a saturated or unsaturated hydrocarbon group of C1 to C8, a cycloalkyl group of C3 to C12, and an aryl group of C6 to C18, preferably from at least one of a saturated alkyl group of C1 to C5, a cycloalkyl group of C3 to C8, and an aryl group of C6 to C10; more preferably, the trialkylsilylphenol compound is selected from at least one of 2-(trimethylsilyl)phenol, 2-(triethylsilyl)phenol, and 4-(trimethylsilyl)phenol.
[0009] According to embodiments of the present invention, the electron-donating compound is selected from at least one of esters, ethers, and ketones, preferably from at least one of alkyl esters of C1-C6 saturated fatty carboxylic acids, alkyl esters of C7-C10 aromatic carboxylic acids, C2-C6 fatty ethers, C3-C6 cyclic ethers, and C3-C12 saturated fatty ketones, more preferably from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, diethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, and most preferably from at least one of methyl formate, ethyl acetate, butyl acetate, diethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, especially tetrahydrofuran.
[0010] According to embodiments of the present invention, the inorganic oxide carrier can be conventionally selected according to the prior art, and can be selected from at least one of silicon oxide and aluminum oxide, preferably from at least one of alumina and silicon dioxide, and more preferably from silicon dioxide; specifically, it can be used in solid form or in dispersion form, such as commercially available silica gel products; the particle size of the inorganic oxide carrier is 0.005 to 12 μm, preferably 0.01 to 8 μm, and more preferably 0.01 to 1 μm.
[0011] According to an embodiment of the present invention, the magnesium halide is selected from at least one of magnesium chloride, magnesium bromide, and magnesium iodide;
[0012] The titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide and titanium tetrabromide, preferably selected from at least one of titanium trichloride and titanium tetrachloride.
[0013] According to an embodiment of the present invention, the content of the inorganic oxide support in the catalyst system, by mass percentage, is 5% to 50%, for example, it can be 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50%, or any value or range between any two of the above values; preferably, the content of the inorganic oxide support is 10% to 35%, more preferably 15% to 30%;
[0014] The titanium content in the catalyst system is 0.1% to 5.5% by mass, for example, it can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or 5.5%, or any value or range between any two of the above values; preferably, the titanium content in the catalyst system is 0.5% to 4.5%, more preferably 1.5% to 3%;
[0015] The magnesium halide, calculated per mol of titanium halide, is 0.1–16 mol, for example, it can be 0.1, 0.5, 1, 2, 5, 9, 10, 12, 15, or 16 mol, or any value or range between any two of the above values. Preferably, the magnesium halide is 1–12 mol, more preferably 2–9 mol; the trialkylsilylphenol compound is 0.01–12 mol, for example, it can be 0.01, 0.02, 0.1, 0.2, 0.5, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 mol, or the above. The value or range between any two values is preferred, the trialkylsilylphenol compound is 0.05-10 mol, more preferably 0.1-5 mol; the electron donor compound is 1-500 mol, for example, it can be 1, 10, 15, 20, 50, 100, 150, 200, 220, 250, 270, 300, 350, 400, 450 or 500 mol, or the value or range between any two values is preferred, the electron donor compound is 20-270 mol, more preferably 100-220 mol.
[0016] A second objective of this invention is to provide a method for preparing the above-mentioned catalyst system containing trialkylsilylphenol compounds, comprising:
[0017] (1) The mother liquor is obtained by reacting the components including trialkylsilylphenol compounds, magnesium halides, titanium halides, and electron donor compounds.
[0018] (2) Add the inorganic oxide carrier to the mother liquor obtained in step (1) to obtain a slurry, and spray dry it to obtain the catalyst system.
[0019] Specifically, in the above method for preparing the catalyst system containing trialkylsilylphenol compounds, in step (1):
[0020] The reaction conditions are: reaction temperature 50–80℃, reaction time 2–5 h;
[0021] Based on each mol of titanium halide, the magnesium halide is 0.1–16 mol, preferably 1–12 mol, more preferably 2–9 mol; the trialkylsilylphenol compound is 0.01–12 mol, preferably 0.05–10 mol, more preferably 0.1–5 mol; and the electron donor compound is 1–500 mol, preferably 20–270 mol, more preferably 100–220 mol.
[0022] In step (2):
[0023] The spray drying can employ commonly used spray drying equipment and drying process conditions in the art. Preferably, the spray drying conditions include: an inlet temperature of 80–240°C, more preferably 120–220°C; and an outlet temperature of 60–130°C, more preferably 90–110°C.
[0024] The inorganic oxide carrier is dried using a conventional drying process and then mixed with the reaction product of magnesium halide, trialkylsilylphenol compounds, titanium halide and electron donor compounds to form a slurry suitable for spray drying; wherein, by mass percentage, the content of the inorganic oxide carrier in the slurry is 0.5-50%, preferably 1-30%.
[0025] A third objective of this invention is to provide a catalyst for olefin polymerization, obtained by mixing the following components:
[0026] Component (A): Organoaluminum compound;
[0027] Component (B): The catalyst system containing trialkylsilylphenol compounds described above or the catalyst system containing trialkylsilylphenol compounds obtained by the above preparation method.
[0028] According to an embodiment of the present invention, in the catalyst for olefin polymerization:
[0029] The organoaluminum compound has the general formula AlR n X 3-n In the formula, R is a C1-C20 hydrocarbon group, preferably a C1-C10 hydrocarbon group; X is a halogen, preferably chlorine; 0 < n ≤ 3; more preferably, the organoaluminum compound can be selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum chloride;
[0030] The molar ratio of aluminum in component (A) to titanium in component (B) is (2-400):1, preferably (10-200):1;
[0031] The catalyst is obtained by mixing the organoaluminum compound of component (A) and the catalyst system containing trialkylsilylphenol compounds of component (B). There are no particular limitations on the mixing method, and any commonly used mixing equipment can be used.
[0032] A fourth objective of this invention is to provide an application of the aforementioned catalyst for olefin polymerization in olefin polymerization reactions. Specifically, the catalyst is added to a polymerization reaction system containing a hydrocarbon organic solvent, where it is activated and then initiates the olefin polymerization reaction. The hydrocarbon solvent includes, but is not limited to, isopentane, hexane, heptane, toluene, xylene, naphtha, and mineral oil.
[0033] To make the solid catalyst component obtained after spray drying suitable for the production of ethylene polymers, an activator component (e.g., an organoaluminum compound) is used to reduce the titanium atoms in the catalyst component to a state that allows for the effective polymerization of ethylene. Generally, the catalyst component and the activator component are reacted in a hydrocarbon solvent to obtain a catalyst capable of catalyzing olefin polymerization; alternatively, the catalyst component and the activator component can be added to the reaction system during polymerization and reacted in a hydrocarbon organic solvent to initiate the olefin polymerization reaction.
[0034] The catalyst of this invention is suitable for homopolymerization of various ethylenes or copolymerization of ethylene with α-olefins, wherein the α-olefins can be selected from propylene, butene, pentene, hexene, octene, and 4-methylpentene-1. The polymerization process can employ gas-phase, slurry, and solution methods, with gas-phase fluidized bed polymerization being particularly suitable. The conditions for olefin polymerization can be conventionally selected according to existing technologies and will not be elaborated upon here.
[0035] This invention uses inorganic oxides as a support. An electron-donating compound, magnesium halide, trialkylsilylphenol compounds, and titanium halide are reacted and then added to the support to form a slurry. Finally, a catalyst system supported on trialkylsilylphenol compounds is prepared by spray molding. In olefin polymerization, the catalyst system is activated by organoaluminum compounds to obtain a highly active catalyst. Polymers prepared using this catalyst have a high melt index, low hexane extract content, and low oligomer content. The phenolic groups in the trialkylsilylphenol compounds used in this invention have a strong electron-donating effect, allowing the silicon atoms to coordinate with the active center, effectively improving the polymerization efficiency of the catalyst's active center. Detailed Implementation
[0036] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0037] The testing instruments and conditions used in this embodiment are as follows:
[0038] 1. Catalyst activity: expressed as the weight of polymer obtained per gram of catalyst;
[0039] 2. Polymer melt index (MI): Model 6932 melt indexer, CEAST, Italy;
[0040] 3. Hexane extractable content (wt%) in polymer powder: The dried polymer powder is extracted with hexane. Specifically, the polymer is washed with hexane for 4 hours. The percentage of the weight difference of the polymer powder before and after extraction relative to the weight of the polymer powder before extraction is the hexane extractable content in the polymer powder.
[0041] 4. Determination of titanium content in catalyst components: Dissolve the catalyst sample in 1M sulfuric acid, measure the solution using a spectrophotometer, and calculate the titanium content using the working curve;
[0042] 5. The content of inorganic oxides can be obtained by calculating the ratio of the feed amount to the mass of the produced catalyst.
[0043] All raw materials used in the examples are commercially available products.
[0044] Example 1
[0045] (1) Preparation of catalyst system
[0046] 2.25 g TiCl4, 6.0 g anhydrous MgCl2, 1.1 g 2-trimethylsilylphenol and 150 mL tetrahydrofuran were added sequentially to a 250 mL three-necked flask purged with nitrogen. The mixture was stirred and heated to 65 °C, and reacted at this temperature for 3 hours. The mixture was then cooled to 35 °C to obtain the mother liquor.
[0047] 9 g of silica gel (Cabot Corporation TS-610, particle size 0.02–0.1 μm) was added to a 250 mL three-necked flask purged with nitrogen. The cooled mother liquor was then added, and the temperature was maintained at 35 °C. After stirring for 1 hour, the silica gel-blended mother liquor was spray-dried using a spray dryer under the following conditions: inlet temperature 195 °C and outlet temperature 110 °C, to obtain the catalyst system, in which the titanium content was 2.24 wt% and the silica content was 24 wt%.
[0048] (2) Ethylene slurry polymerization
[0049] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, along with 4mL of 1M triethylaluminum / hexane and 0.02g of the catalyst system obtained above. The temperature was raised to 75℃, and hydrogen gas was added at 0.18MPa. After hydrogenation, ethylene gas at 0.75MPa was added, and the temperature was raised to 85℃. After reacting for 2 hours, the mixture was cooled and discharged. The polymerization results are shown in Table 1.
[0050] Example 2
[0051] (1) Preparation of catalyst system
[0052] Same as Example 1, except that: the amount of 2-trimethylsilylphenol used is 2.2g, the titanium content of the obtained catalyst component is 2.25wt%, and the silicon dioxide content is 24wt%.
[0053] (2) Ethylene slurry polymerization
[0054] Same as Example 1, the polymerization results are shown in Table 1.
[0055] Example 3
[0056] (1) Preparation of catalyst system
[0057] Same as Example 1, except that the amount of 2-trimethylsilylphenol used is 0.6g, the titanium content of the obtained catalyst component is 2.19wt%, and the silicon dioxide content is 25wt%.
[0058] (2) Ethylene slurry polymerization
[0059] Same as Example 1, the polymerization results are shown in Table 1.
[0060] Example 4
[0061] (1) Preparation of catalyst system
[0062] Same as Example 1, except that 2-trimethylsilylphenol is replaced with 2-triethylsilylphenol, and the amount used is 0.7g. The resulting catalyst component has a titanium content of 2.22wt% and a silicon dioxide content of 23wt%.
[0063] (2) Ethylene slurry polymerization
[0064] Same as Example 1, the polymerization results are shown in Table 1.
[0065] Comparative Example 1
[0066] (1) Preparation of catalyst system
[0067] 2.25 g TiCl4, 6.0 g anhydrous MgCl2 and 150 mL tetrahydrofuran were added to a 250 mL three-necked flask purged with nitrogen. The mixture was stirred and heated to 65 °C. The mixture was then kept at this temperature for 3 hours and cooled to 35 °C to obtain the mother liquor.
[0068] 9g of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1μm) was added to a 250mL three-necked flask purged with nitrogen. The cooled mother liquor was then added, and the temperature was maintained at 35℃. After stirring for 1 hour, the mother liquor mixed with silica gel was spray-dried using a spray dryer under the following conditions: inlet temperature 195℃ and outlet temperature 110℃. The resulting catalyst composition contained 2.2wt% titanium and 25wt% silica.
[0069] (2) Ethylene slurry polymerization
[0070] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, along with 2mL of 1M triethylaluminum / hexane and 0.01g of the catalyst system obtained above. The temperature was raised to 75℃, and hydrogen gas was added at 0.18MPa. After hydrogenation, ethylene gas at 0.75MPa was added, and the temperature was raised to 85℃. After reacting for 2 hours, the mixture was cooled and discharged. The polymerization results are shown in Table 1.
[0071] Table 1. Catalyst performance obtained from examples and comparative examples
[0072]
[0073] As can be seen from the polymerization data in Table 1, under the same polymerization conditions, the catalyst obtained by adding trialkylsilylphenol compounds in this invention has higher activity, the resulting polymer has a higher melt index, and the content of hexane extractable is lower.
[0074] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A catalyst system comprising an inorganic oxide support and a product obtained by reacting a trialkylsilylphenol compound, a magnesium halide, a titanium halide, and an electron donor compound; By mass percentage, the inorganic oxide support in the catalyst system is 5-50%, and the titanium content is 0.1-5.5%. Based on each mol of titanium halide, the amount of magnesium halide is 0.1~16 mol, the amount of trialkylsilylphenol compound is 0.01~12 mol, and the amount of electron donor compound is 1~500 mol.
2. The catalyst system according to claim 1, characterized in that, The general formula of the trialkylsilylphenol compounds is R3Si-Ph-OH, wherein R is selected from at least one of H, C1-C8 saturated or unsaturated hydrocarbon groups, C3-C12 cycloalkyl groups, and C6-C18 aryl groups; and / or, The electron-donating compound is selected from at least one of esters, ethers, and ketones; and / or, The inorganic oxide support is selected from at least one of silicon oxides and aluminum oxides; and / or, The inorganic oxide support has a particle size of 0.005~12μm; and / or, The magnesium halide is selected from at least one of magnesium chloride, magnesium bromide, and magnesium iodide; and / or, The titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide, and titanium tetrabromide.
3. The catalyst system according to claim 2, characterized in that, The general formula of the trialkylsilylphenol compounds is R3Si-Ph-OH, wherein R is selected from at least one of C1-C5 saturated alkyl, C3-C8 cycloalkyl, and C6-C10 aryl; and / or, The electron-donating compound is selected from at least one of the following: alkyl esters of C1-C6 saturated fatty carboxylic acids, alkyl esters of C7-C10 aromatic carboxylic acids, C2-C6 fatty ethers, C3-C6 cyclic ethers, and C3-C12 saturated fatty ketones; and / or, The inorganic oxide support is selected from at least one of alumina and silicon dioxide; and / or, The inorganic oxide support has a particle size of 0.01~8μm; and / or, The titanium halide is selected from at least one of titanium trichloride and titanium tetrachloride.
4. The catalyst system according to claim 2, characterized in that, The trialkylsilylphenol compounds are selected from at least one of 2-(trimethylsilyl)phenol, 2-(triethylsilyl)phenol, and 4-(trimethylsilyl)phenol; and / or, The electron-donating compound is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, diethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone; and / or, The inorganic oxide carrier is silicon dioxide; and / or, The particle size of the inorganic oxide support is 0.01~1μm.
5. The catalyst system according to claim 4, characterized in that, The electron-donating compound is selected from at least one of methyl formate, ethyl acetate, butyl acetate, diethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone.
6. The catalyst system according to claim 1, characterized in that, The inorganic oxide support in the catalyst system is 10-35% by mass percentage; and / or, The titanium content in the catalyst system is 0.5% to 4.5% by mass; and / or, Based on each mol of titanium halide, the amount of magnesium halide is 1~12 mol, the amount of trialkylsilylphenol compound is 0.05~10 mol, and the amount of electron donor compound is 20~270 mol.
7. The catalyst system according to claim 6, characterized in that, The inorganic oxide support in the catalyst system is 15-30% by mass percentage; and / or, The titanium content in the catalyst system is 1.5-3% by mass; and / or, Based on each mol of titanium halide, the amount of magnesium halide is 2-9 mol, the amount of trialkylsilylphenol compound is 0.1-5 mol, and the amount of electron donor compound is 100-220 mol.
8. A method for preparing the catalyst system according to any one of claims 1 to 7, comprising: (1) The mother liquor is obtained by reacting the components, which include trialkylsilylphenol compounds, magnesium halides, titanium halides and electron donor compounds; (2) Add an inorganic oxide carrier to the mother liquor obtained in step (1) and mix to obtain a slurry. After spray drying, the catalyst system is obtained.
9. The preparation method according to claim 8, characterized in that, The reaction conditions in step (1) are: a reaction temperature of 50~80℃ and a reaction time of 2~5h; and / or, By mass percentage, the inorganic oxide carrier content in the slurry of step (2) is 0.5-50%; and / or, The conditions for spray drying in step (2) include: inlet temperature of 80~240℃ and outlet temperature of 60~130℃.
10. The preparation method according to claim 9, characterized in that, By mass percentage, the content of inorganic oxide carrier in the slurry of step (2) is 1-30%; and / or, The spray drying conditions in step (2) include: an inlet temperature of 120~220℃ and an outlet temperature of 90~110℃.
11. A catalyst for olefin polymerization, obtained by mixing the following components: Component (A): Organoaluminum compound; Component (B): The catalyst system according to any one of claims 1 to 7 or the catalyst system obtained by the preparation method according to any one of claims 8 to 10.
12. The catalyst according to claim 11, characterized in that, The organic aluminum compound has a general formula of AlR n X 3-n wherein R is a C1-C20 hydrocarbon group, X is a halogen, and 0 The molar ratio of aluminum in component (A) to titanium in component (B) is (2~400):
1.
13. The catalyst according to claim 12, characterized in that, The organic aluminum compound has a general formula of AlR n X 3-n wherein R is a C1-C10 hydrocarbon group, and X is chlorine; and / or, The molar ratio of aluminum in component (A) to titanium in component (B) is (10~200):
1.
14. The catalyst according to claim 13, characterized in that, The organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum chloride.
15. The use of the catalyst according to any one of claims 11 to 14 in olefin polymerization reactions.
Citation Information
Patent Citations
Polymerization of ethylene catalyst component having high output ratio, preparation and use
CN101376680A
Catalyst component and catalyst for olefin polymerization, and preparation methods thereof
CN106543303A
Olefin polymerization catalyst and preparation method thereof
CN101845104A
Catalyst component used for olefin polymerization, catalyst, and preparation method of catalyst component
CN106543316A
